DEVELOPING POP UP HANDOUTS AS READING MATERIALS IN TEACHING NARRATIVE TEXT - Prilini, Desi Fatima; Salam, Urai; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The purpose of this study was to develop reading materials in form of Pop Up handouts. The method applied by the researcher was ADDIE method which covered five phases; analysis, design, development, implementation, and evaluation. Pop Up handouts played a role as a supplementary material in teaching reading narrative text. Pop Up handouts are books that consist of two stories and sets of three dimensional pictures which are able to fold and rise automatically. The thick papers were used as the basis for the texts and the illustration. The illustrations of the handouts were originally designed by the researcher. The study was conducted at SMPN 19 Pontianak in academic year 2015/2016. From evaluation phase, Pop Up handouts achieved a satisfying score based on the validation by the experts which was classified as very good with 85% without any revision. Besides, the product was applicable to be used by the teachers to teach narrative text. Keywords: Pop Up handouts, Reading Material, Designing Material Abstrak: Penelitian ini bertujuan untuk mengembangkan materi baca dalam bentuk Pop Up handouts. Metode yang diterapkan oleh peneliti adalah metode ADDIE yang mencakup lima tahap penelitian; analisis, pembuatan, pengembangan, penerapan, dan evaluasi. Pop Up handouts berperan sebagai materi tambahan dalam mengajar bacaan teks naratif. Pop Up handouts merupakan buku yang berisi dua buah cerita serta gambar-gambar tiga dimensi yang dapat dilipat dan berdiri secara otomatis. Kertas tebal digunakan sebagai dasar untuk teks dan ilustrasinya. Ilustrasi-ilustrasi dalam Pop Up handouts secara murni dibuat oleh peneliti sendiri. Penelitian ini dilakukan di SMPN 19 Pontianak pada tahun ajaran 2015/2016. Dari tahap terakhir, yaitu tahap evaluasi, Pop Up handouts mencapai hasil yang sangat memuaskan dengan skor 85% tanpa ada perbaikan. Selain itu, produk ini terbukti dapat digunakan oleh guru untuk mengajar teks naratif. Keywords: Pop Up handouts, Materi Bacaan, Pembuatan Materi